Household Vulnerability to Income Shocks in Emerging and Developing Asia : The Case of Cambodia, Nepal and Vietnam - De Stefani, Alessia; Laws, Athene; Sollaci, Alex. (Washington, D.C. : International Monetary Fund, 2022)
We leverage survey data from emerging and developing Asia to highlight different aspects of household vulnerability to income shocks arising from the Covid-19 pandemic: occupation in Cambodia, self-insurance mechanisms in Nepal, and financial leverage in Vietnam. Occupation and ex-ante income levels emerge as the main drivers of vulnerability. We estimate that the pandemic could have placed an additional 6 to 9 percent of the population of each country in a vulnerable position, with the impact concentrated on urban, informal, and service sector workers. Government intervention and financial access emerge as key resilience-enhancing mechanisms.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Consumer Economics; Economics; Income Shocks; Macroeconomics; Personal Finance